1976
DOI: 10.1111/j.1432-1033.1976.tb10022.x
|View full text |Cite
|
Sign up to set email alerts
|

Circular-Dichroism Spectra of Truncated and Other Analogs of Angiotensin II

Abstract: Circular dichroism spectra on angiotensin I1 and analogs, and its truncated N-terminal and C-terminal peptides were determined in fluorinated alcohols under several conditions in the peptide or aromatic spectral regions. The following conclusions were suggested : (a) evidence for a structure for angiotensin 11; (b) evidence for a folding at the N-terminal and C-terminal part of the molecule; (c) an interaction involving the C-terminal residue which decreases progressively when phenylalanine is replaced by isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 20 publications
0
32
0
1
Order By: Relevance
“…Whereas the pH dependence of the difference spectra is well correlated between the ' L b and 'Lo, ' B bands in these peptides, it is surprising that the rather remarkable solvent effect of FsEtOH in the near-ultraviolet CD spectra is so weakly evident in the peptide region, especially with respect to residue 8. In this context we are reminded of the fact that the solvent effect H,0/F3EtOH for the entire far-ultraviolet CD spectrum of bradykinin, as shown by Marlborough et al [9] and confirmed by our studies, is rather small in comparison to what has been observed in the case of angiotensin 11 [26] and adrenocorticotropin [27]. Evidently the three transitions 'Lb, ' L , and ' B are not affected equally every time an outer parameter changes in any way.…”
Section: Spectra In the Far-ultraviolet Regionmentioning
confidence: 42%
“…Whereas the pH dependence of the difference spectra is well correlated between the ' L b and 'Lo, ' B bands in these peptides, it is surprising that the rather remarkable solvent effect of FsEtOH in the near-ultraviolet CD spectra is so weakly evident in the peptide region, especially with respect to residue 8. In this context we are reminded of the fact that the solvent effect H,0/F3EtOH for the entire far-ultraviolet CD spectrum of bradykinin, as shown by Marlborough et al [9] and confirmed by our studies, is rather small in comparison to what has been observed in the case of angiotensin 11 [26] and adrenocorticotropin [27]. Evidently the three transitions 'Lb, ' L , and ' B are not affected equally every time an outer parameter changes in any way.…”
Section: Spectra In the Far-ultraviolet Regionmentioning
confidence: 42%
“…Although it could be argued that the structural transition to ␣-helix seen here may be due to the ␣-helical stabilizing effects of organic solvents such as TFE (33), there are a number of observations that support the conclusion of a genuine propensity for the M. tuberculosis Cpn10 monomer to form partially helical structures. Firstly, regions without helical propensity do not form helices even in 100% TFE (26,43), and other structures (e.g., ␤-turn and ␤-sheet) are supported by this solvent (14,15,42). Secondly, a partially helical monomer exists also in the absence of organic solvents, albeit at a very low concentration (Fossati et al, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…Conformational analysis indicates that the angiotensin peptides with a greater antiplasmodial activity form a β structure [8]. Analogs 1 and 8 also had a tendency to form β structures.…”
Section: Resultsmentioning
confidence: 99%